Antimicrobial efficacy of different natural extracts against persistent root canal pathogens: An In vitro study - M C Noushad; Biji Balan; Shabhana Basheer; Shinsus Bin Usman; M K Muhammed Askar (Wolters Kluwer Medknow Publications, 2018)
Introduction: The spread of drug-resistant pathogens is one of the most serious threats to successful treatment of microbial diseases. Extracts of plants such as flowers, buds, seeds, leaves, twigs, bark, herbs, wood, fruits, and roots have evoked interest as sources of natural products. Irrigation with a broad-spectrum antiseptic substance and inter-appointment intracanal medication has become a standard regimen in root canal therapy. Aim: The aim of this study is to compare the antimicrobial efficacy of different natural extracts such as guava leaf extract, Aloe vera extract, papaya leaf extract, and cashew apple extract against Enterococcus faecalis and Candida albicans. Materials and Methods: The antimicrobial activity was determined using agar diffusion test. The solutions were divided into four groups: Group I - guava leaf extract, Group II - A. vera extract, and Group III - papaya leaf extract, and Group IV - cashew apple extract. The zones of inhibition of growth were recorded. The strains used for this study were E. faecalis ATCC 29212 and C. albicans ATCC 90028. Results and Conclusion: Sodium hypochlorite had demonstrated the best results among the tested solutions. Among the herbal extracts, cashew apple extract and guava leaf extract had shown statistically significant activity against E. faecalis and C. albicans.